EFFECT OF PRICE, QUALITY PRODUCTS AND QUALITY OF CUSTOMER SATISFACTION LEVEL PRINTING PT. UBC DIBATAM - Aisyah A; Yannik Ariyati (BENING, 2015)
This research was conducted at PT. UBC Batam. The purpose of this study was to determine the effect of pricing, product quality and service quality to customer satisfaction levels together (simultaneously).          In this study, the authors use census method with a total of 60 people to serve as respondents of the total population. While this type of data used are primary data and secondary data. Sources of primary data obtained from the questionnaire to the Employee At PT. UBC Batam. While secondary data obtained from the document PT. UBC Batam and obtained from the literature related and can support as well as useful for this study. Data was collected through interviews, questionnaires and documentation. Data analysis was performed with descriptive statistics, which is used to describe in giving an overview of the object under study through the data with census method taken from the population obtained in the field associated with theories that are relevant and techniques of quantitative analysis of the data that has been given a score according to measurement scale used is Likert scale and the test results using SPSS (Statistical Product and Service Solution) version 20.          From the results of the study authors conclude that the simultaneous price (X1), product quality (X2) and quality of service (X3) positive and significant impact on customer satisfaction (Y), with the result of 304.353 with a significance level of 0.000.